2015
DOI: 10.1039/c4ob02511c
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular control of transition metal complexes in water by a hydrophobic cavity: a bio-inspired strategy

Abstract: Supramolecular chemistry in water is a very challenging research area. In biology, water is the universal solvent where transition metal ions play major roles in molecular recognition and catalysis. In enzymes, it participates in substrate binding and/or activation in the heart of a pocket defined by the folded protein. The association of a hydrophobic cavity with a transition metal ion is thus a very appealing strategy for controlling the metal ion properties in the very competitive water solvent. Various sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
55
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 80 publications
0
55
0
1
Order By: Relevance
“…14 Concurrently to the strategies developed in organic media, we demonstrated that the supramolecular approach was applicable to water-soluble bidentate ligands through hydrophobic effects using an appropriate cyclodextrin (CD)/phosphane combination. 15,16,17,18 More precisely, we showed that CDs functionalized on their primary face by nitrogen donor groups could partially include within their cavity a water-soluble sulfonated phosphane to form supramolecular PN ligands. The resulting self-assembled entities were capable of coordinating platinum and rhodium complexes in a κ 2 -P,N coordination mode, the CD simultaneously acting as a first-and secondsphere ligand (Scheme 1).…”
Section: Introductionmentioning
confidence: 91%
“…14 Concurrently to the strategies developed in organic media, we demonstrated that the supramolecular approach was applicable to water-soluble bidentate ligands through hydrophobic effects using an appropriate cyclodextrin (CD)/phosphane combination. 15,16,17,18 More precisely, we showed that CDs functionalized on their primary face by nitrogen donor groups could partially include within their cavity a water-soluble sulfonated phosphane to form supramolecular PN ligands. The resulting self-assembled entities were capable of coordinating platinum and rhodium complexes in a κ 2 -P,N coordination mode, the CD simultaneously acting as a first-and secondsphere ligand (Scheme 1).…”
Section: Introductionmentioning
confidence: 91%
“…It has been found that supramolecular assemblies could stabilize reactive metal complexes and increase their turn over numbers (Brown et al, 2011). Additionally, supramolecular complexes enable the catalytic activity of several transition metal catalysts in water by providing a bio-inspired hydrophobic cavity (Bistri et al, 2015; Kaphan et al, 2015; Pluth et al, 2007). Importantly, supramolecular cage prevents the direct interaction of transition metal with enzymes, thereby averting their mutual inactivation (Kohler et al, 2013; Wang et al, 2013).…”
Section: Tandem Chemo-enzymatic Reactionsmentioning
confidence: 99%
“…Creation of supramolecular hosts with hydrophobic cavities and a transition metal complex is a very appealing strategy for controlling the metal complex properties in competitive water solvents containing proteins and other cellular components [111]. Similarly, artificial metalloenzymes have been further developed to integrate transition-metal catalysts into cascade reactions with other biocatalysts and foster bioorthogonal transformations catalyzed by metal complexes in living cells.…”
Section: Future Prospects and Conclusionmentioning
confidence: 99%